Connecting genomic results for psychiatric disorders to human brain cell types and regions reveals convergence with functional connectivity - Shuyang Yao; Arvid Harder; Fahimeh Darki; Yu-Wei Chang; Ang Li; Kasra Nikouei; Giovanni Volpe; Johan N. Lundström; Jian Zeng; Naomi R. Wray; Yi Lu; Patrick F. Sullivan; et al. (Nature Communications)
Abstract Identifying cell types and brain regions critical for psychiatric disorders and brain traits is essential for targeted neurobiological research. By integrating genomic insights from genome-wide association studies with a comprehensive single-cell transcriptomic atlas of the adult human brain, we prioritized specific neuronal clusters significantly enriched for the SNP-heritabilities for schizophrenia, bipolar disorder, and major depressive disorder along with intelligence, education, and neuroticism. Extrapolation of cell-type results to brain regions reveals the whole-brain impact of schizophrenia genetic risk, with subregions in the hippocampus and amygdala exhibiting the most significant enrichment of SNP-heritability. Using functional MRI connectivity, we further confirmed the significance of the central and lateral amygdala, hippocampal body, and prefrontal cortex in distinguishing schizophrenia cases from controls. Our findings underscore the value of single-cell transcriptomics in understanding the polygenicity of psychiatric disorders and suggest a promising alignment of genomic, transcriptomic, and brain imaging modalities for identifying common biological targets.